Analisis Daya Saing Perkebunan Kelapa Sawit Pola Swadaya Kabupaten Tanjung Jabung Barat - Akbar, Guntur Aulia; Nainggolan, Saidin (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Independent plantations are a favorite in the Jambi Regional economy, as they are a source of economic growth, employment, exports, and foreign exchange for the region. Despite their relatively low productivity, oil palm plantations in Jambi Province have a major competitive advantage compared to other commodities. This study aims to describe, analyze competitiveness, analyze policy impacts, and conduct sensitivity tests on independent oil palm plantations. The research location was in Merlung District, selecting three sample villages: Tanjung Paku Village, Merlung Village, and Lubuk Terap Village purposively, with a total sample of 43 farmers. The data analysis method used the (PAM) method. The results of the analysis show that independent farmers still have relatively low productivity. The DRCR value is 0.379 (<1) and the PCR value is 0.368 (<1) which indicates savings in the use of domestic resources by 37.9% and 36.8%. These results indicate a comparative and competitive advantage. The divergence impact shows a negative impact, meaning that government policies are not distorted properly, as indicated by an NPCI value of 1.18 (> 1) and an NPCO value of 0.87 (< 1). Sensitivity tests show that independent oil palm plantations still have competitiveness (< 1), despite experiencing policy distortions such as input price increases (11% and 25%) and a decrease in FFB prices (45%).